Helicobacter pylori infection induces gastric precancerous lesions and persistent expression of Angpt2, Vegf-A and Tnf-A in a mouse model - Malespín-Bendaña, Wendy; Alpízar-Alpízar, Warner; Figueroa-Protti, Lucía; Reyes, Ledis; Molina-Castro, Silvia; Une, Clas; Ramírez-Mayorga, Vanessa (Frontiers in Oncology, 2023)
Helicobacter pylori colonizes the gastric mucosa and induces chronic inflammation. Using a mouse model of H. pylori-induced gastritis, we evaluated the mRNA and protein expression levels of proinflammatory and proangiogenic factors, as well as the histopathological changes in gastric mucosa in response to infection. Five- to six-week-old female C57BL/6N mice were challenged with H. pylori SS1 strain. Animals were euthanized after 5-, 10-, 20-, 30-, 40- and 50-weeks post infection. mRNA and protein expression of Angpt1, Angpt2, VegfA, Tnf-α, bacterial colonization, inflammatory response and gastric lesions were evaluated. A robust bacterial colonization was observed in 30 to 50 weeks-infected mice, which was accompanied by immune cell infiltration in the gastric mucosa. Compared to non-infected animals, H. pylori-colonized animals showed an upregulation in the expression of Tnf-A, Angpt2 and VegfA at the mRNA and protein levels. In contrast, Angpt1 mRNA and protein expression was downregulated in H. pylori-colonized mice. Our data show that H. pylori infection induces the expression of Angpt2, Tnf-A and Vegf-A in murine gastric epithelium. This may contribute to the pathogenesis of H. pylori-associated gastritis, however the significance of this should be further addressed.